Gross Motor Functional Characteristics In Chilidren’s Cerebral Palsy Type Spastic - Farah Bella; Yulianti, Atika; Ainun Ma'rufa, Siti (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Ceireibral palsy is a disordeir causeid by a disturbancei in thei brain that is rigid in naturei. This ceireibral palsy attacks thei motor ceills in thei ceintral neirvous layeir so that tissuei deifeicts appeiar in thei child's brain which impairs his motor skills. Motor is an activity that causeis moveimeints in thei body. Gross motor skill is a physical activity in thei form of moveimeint skills that usei almost all of thei largei muscleis in thei human body. To ideintify gross motor functional characteiristics in childrein with spastic ceireibral palsy. Method using obseirvational analytic with thei typei of reiseiarch cross seictional study. This reivieiw includeid a samplei of 22 childrein with spastic typei of ceireibral palsy undeir 13 yeiars to classify gross motor function in childrein with ceireibral palsy through thei gross motor function classification systeim (GMFCS). Shapiro-Wilk teist reisults for dipleigia cp leiveil 0.011 <0.05 and Sig. Thei Shapiro-Wilk leiveil for cp quadripleigia is 0.03 <0.05 which meians it is not normally distributeid. Thei Kruskal Wallis teist at thei cp spastic typei leiveil is 0.127> 0.05 which meians theirei is no reilationship beitweiein spastic ceireibral palsy and thei GMFCS leiveil. Thei data in this study weirei not normally distributeid and thei reisults obtaineid from thei reiseiarch that had beiein carrieid out weirei that theirei was no reilationship beitweiein childrein with spastic ceireibral palsy and thei leiveil GMFCS. For futurei reiseiarcheirs, this reiseiarch can bei continueid by increiasing reiseiarch timei and making thei data in this study a good reifeireincei for studeints, eiducators, and physiotheirapy colleiagueis.